Potential for increasing groundnut production in Tanzania by enhancing technical efficiency: A stochastic meta-frontier analysis - Das, Abhishek; Kumar, Shalander; Ganga Rao, N. V. P. R. (Frontiers in Sustainable Food Systems, 2023)
Groundnut is among the most important crops for smallholder farmers in Tanzania, contributing to household food and income security. Nevertheless, groundnut production in Tanzania is not well developed, and yields are reported to be 2.5 to 3 times lower compared with other African countries such as Nigeria. The use of obsolete varieties, unreliable rains, disease, insect pests’ infestation, and poor agronomic practices are some of the causes. To analyze the scope for increasing groundnut production, this study investigates and compares the technical efficiencies (TEs) and technological gap ratios (TGRs) in Tanzania's four main groundnut-producing regions, namely the Central zone, Lake Zone, Southern zone, Southern highland zone, by using a two-step meta frontier model. We used ICRISAT data collected under the Tropical Legume-III project during 2017-18. Our results show a very low level of technical efficiency in the regions and significant regional differences in TEs, TGRs, and meta-technical efficiencies (MTEs). The study identifies a tremendous scope to increase groundnut productivity and production in Tanzania by enhancing its production efficiency and the key drivers that may help harness this potential.